TWO NEW SPECIES AND ONE NEW GEOGRAPHICAL RECORD FOR SARAWAK, MALAYSIA (CYPERACEAE: MAPANIOIDEAE) - MIRAADILA MOHD. ISA; ZINNIRAH SHABDIN; MEEKIONG KALU (REINWARDTIA, 2016)
MIRAADILA, M. I., SHABDIN, Z. & MEEKIONG, K. 2016. Two new species and one new geographical record for Sarawak, Malaysia (Cyperaceae: Mapanioideae). Reinwardtia 15(2): 129 – 135. — Mapania hidiriana and M. sembilingensis, two new species from Sarawak, Malaysia are described and illustrated. Mapania hidiriana can be differentiate from M. meditensis by elongated lanceolate inflorescences. Whilst, M. sembilingensisis differ from M. multiflora and M. hispida by the floral and fruit morphologies. In additional, M. spadicea Uittien, a new geographical record for Sarawak is also presented.